Integrating AI-TPACK for Pre-Service Teachers: Applications and Challenges in English Language Program - Ramadhani, Pungky; Amalia, Eka Rizki; Kusrini, Nurul Azizah Ria (Journal of Nusantara Education, 2026)
Artificial Intelligence (AI) is transforming education, offering innovative opportunities to enhance teaching and learning. Integrating AI into the Technological Pedagogical Content Knowledge (TPACK) framework has led to the development of AI-TPACK, which addresses the specific skills and strategies required for effective AI integration in educational contexts. While existing research focuses primarily on teachers’ readiness to adopt AI, limited attention has been given to pre-service teachers (PSTs) and their practical application of AI-TPACK. This study explores how PSTs in an English Language Program apply AI-TPACK in their teaching practices and investigates the challenges they encounter during implementation. Employing a narrative inquiry approach, the study collects data through questionnaires, semi-structured interviews, and reflective journals. Questionnaires assess PSTs' theoretical and practical understanding of AI-TPACK, while interviews provide in-depth insights into their lived experiences and challenges. Reflective journals capture ongoing reflections, documenting their evolving perspectives and skills. Thematic analysis is used to triangulate data across these sources, ensuring a robust understanding of PSTs’ competencies and challenges in applying AI-TPACK. The findings indicate that AI-TPACK improves PSTs' ability to design lessons, adjust teaching methods, and create more engaging and interactive learning experiences. AI tools also enable more personalized learning by modifying content and adjusting the speed of instruction to meet individual student needs, enhancing both teaching efficiency and student outcomes.